A Tour Through the Whole Island of Great Britain . . ., de Daniel Defoe, e a Escrita de Viagens - Alarcão, Miguel (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
The centrality of the work whose 3rd centenary is celebrated in 2019 - Robinson Crusoe, 1719 - should not make us forget the renovated relevance and interest of other texts by Daniel Defoe (c.1660-1731), such as, for example, The Shortest Way with the Dissenters (1702), for those who want to reflect on religious (in)tolerance; The True-Born Englishman (1701), which may be related to policies and practices of ethnic-racial segregation, mass migrations or the multicultural dimension of contemporary identities and societies; or A Tour Through the Whole Island of Great Britain (1724-26, 3 vols.), which will be the central theme of this paper.